Comprehensive Model for Physical and Cognitive Frailty: Current Organization and Unmet Needs - Lauretani, Fulvio; Longobucco, Yari; Ferrari Pellegrini, Francesca; De Iorio, Aurelio Maria; Fazio, Chiara; Federici, Raffaele; Gallini, Elena; La Porta, Umberto; Ravazzoni, Giulia; Roberti, Maria Federica; Salvi, Marco; Zucchini, Irene; et al. (Frontiers in Psychology, 2020)
Aging represents the decline and deterioration of functional cell resulting in a wide variety of molecular damages and reduced physical and mental capacity. Understanding the pathophysiology of this process is of enormous importance because life expectancy continues to rise and, by 2050, the world’s population aged 60 years and older is expected to reach 2 billion. Aging cannot be considered a homogeneous process, ranging from full performance statuses to frailty and disability, condition where the progressive decline of functional abilities reaches the maximum. Frailty is a dynamic and intermediate condition between a normal functional state and disability. It can be considered as a multidimensional geriatric syndrome characterized by loss of physiological reserves and reduced capacity to recover homeostasis when a stressor event occurs. Frailty affects physical, psychological and social domains and is driven by cognitive, emotional and spiritual components. Sarcopenia is one of the main determinants and the biological substrate of physical frailty. Physical and cognitive frailty have always been considered two separate clinical entities and consequently approached in the clinical practice. The recent introduction in the scientific world of motoric-cognitive syndrome has partially changed this scenario opening interesting windows towards future approaches. The purpose of this paper is to provide an excursus on current clinical practice, moving from pathophysiology and describing concrete case scenarios. The analysis of pros and cons of the current state of art is the basis for supporting the urgent need of comprehensive organizational model including physical and cognitive spheres in the same umbrella.